The association between microRNA-21 and hypertension-induced cardiac remodeling - Watanabe, Ken; Narumi, Taro; Watanabe, Tetsu; Otaki, Yoichiro; Takahashi, Tetsuya; Aono, Tomonori; Goto, Jun; Toshima, Taku; Sugai, Takayuki; Wanezaki, Masahiro; Kutsuzawa, Daisuke; Kato, Shigehiko; et al. (PloS one, 2020)
Hypertension is a major public health problem among the aging population worldwide. It causes cardiac remodeling, including hypertrophy and interstitial fibrosis, which leads to development of hypertensive heart disease (HHD). Although microRNA-21 (miR-21) is associated with fibrogenesis in multiple organs, its contribution to cardiac remodeling in hypertension is poorly understood. Circulating miR-21 level was higher in patients with HHD than that in the control subjects. It also positively correlated with serum myocardial fibrotic markers. MiR-21 expression levels were significantly upregulated in the mice hearts after angiotensin II (Ang II) infusion or transverse aortic constriction (TAC) compared with control mice. Expression level of programmed cell death 4 (PDCD4), a main target of miR-21, was significantly decreased in Ang II infused mice and TAC mice compared with control mice. Expression levels of transcriptional activator protein 1 (AP-1) and transforming growth factor-β1 (TGF-β1), which were downstream targets of PDCD4, were increased in Ang II infused mice and TAC mice compared with control mice. In vitro, mirVana-miR-21-specific inhibitor attenuated Ang II-induced PDCD4 downregulation and contributed to subsequent deactivation of AP-1/TGF-β1 signaling pathway in neonatal rat cardiomyocytes. Thus, suppression of miR-21 prevents hypertrophic stimulation-induced cardiac remodeling by regulating PDCD4, AP-1, and TGF-β1 signaling pathway.